Case Report: Hemorrhagic Central Neurocytoma - Perdawd, Khawand Saeed (International Journal of Health Sciences, 2023)
Central neurocytomas are infrequent tumors, yet they represent the most common primary intraventricular neoplasm among young and middle-aged adults. Their slow growth typically results in detection during the 2nd-4th decades of life, with an even distribution between genders. Due to its rarity and similar features to more common neoplasms, misdiagnosis can pose challenges. Accurate diagnosis often involves radiological imaging, MRS, histopathology, and immunohistochemistry assessments. This was a case report of a 47-year-old man with a right lateral ventricular central neurocytoma accompanied by intraventricular hemorrhage. Surgical intervention through craniotomy resulted in partial mass removal using a transcortical approach. He was referred to the oncology team who recommended radiotherapy. Subsequent hydrocephalus led to a VP shunt placement.